Historical Importance of the Role Played by Jaffna Youth Congress on Jaffna Politics on the 1920S And 1930S - Gamage, C.L. (University of Jaffna, 2018)
- The Jaffna Youth Congress emerged around the early 1920s in Jaffna as an anti-colonial formation. This organization was mainly comprised of educated middle class Tamil youth. It organized various protest activities, boycotts and national cultural programs in the Jaffna peninsula and agitated against imperialism. The members were also strongly against the backward social customs that prevailed in Jaffna society. While emphasizing equality and promoting liberal policies, the Jaffna Youth Congress strongly espoused national unity, ethnic harmony and justice for all the people in the country. Eventually, they focused on achieving ‘PurnaSwaraj’ (Complete Freedom) from British rule. In respect of that, this research mainly intends to find out the historical importance of the Jaffna Youth Congress to Jaffna politics during the 1920s and 1930s period.The data collection mainly depended on secondary sources. This research convincingly revealed that the Jaffna Youth Congress acted as a significant force in the socio political scene of Jaffna during that period. The Youth Congress played a remarkable role in comparison with the main contemporaneous independence movement in the country’s mainstream politics. This latter movement was led by a multi-ethnic, westernized, elite class group that was willing to be a subservient partner under British Dominion rule and never demanded complete freedom, unlike the Jaffna Youth Congress. The Jaffna Youth Congress followed rather radical political methods, but the elite politicians preferred to adopt a conventional political approach. Whereas the Youth Congress insisted on equality based social concepts the elite group showed a lack of concern about the neglected bottom layers of society. Besides, even though all ethnicities were represented in the elite group’s mainstream politics, harmonious relations did not exist between the Sinhala and Tamil elite politicians. Both groups worked towards constitutional privileges focusing on their own ethnic interests. Even though it was just a young Tamil group from the North, the Youth Congress showed great maturity by laying strong emphasis on the importance of ethnic harmony. This is remarkable because that was the most critical historical era during which the grassroots causes of ethnic tensions that later ravaged the country emerged.
Keywords: Radical; Tamil; Unity; Youth Congress